REGIONAL INCOME DIFFERENCES IN BORDERLANDS: A CONVERGENCE ANALYSIS - Guerreiro, Gertrudes (2014)
We intend to answer questions like if geography influences the pattern of inequality, that is, if the standard of living varies from region to region, with special attention to the borders, and if it reveals the presence of spatial correlation. The aim of the paper is to study the regional income differences among the NUTs 3 regions of Portugal and Spain in the borderland of these two countries. After a brief introduction we evaluate the inequalities among borderland regions using information about per capita wages. Considering the neighbourhood relationships between the NUTs 3 regions located in the Portugal-Spain border it is possible to conclude that wages are spatially autocorrelated.